Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1140/epjds/s13688-019-0190-z
|View full text |Cite
|
Sign up to set email alerts
|

Responsible team players wanted: an analysis of soft skill requirements in job advertisements

Abstract: During the past decades the importance of soft skills for labour market outcomes has grown substantially. This carries implications for labour market inequality, since previous research shows that soft skills are not valued equally across race and gender. This work explores the role of soft skills in job advertisements by drawing on methods from computational science as well as on theoretical and empirical insights from economics, sociology and psychology. We present a semi-automatic approach based on crowdsou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 47 publications
4
31
1
Order By: Relevance
“…Fig 5 shows the top words of core skills (general skills) required by DAPET. The abilities mentioned focused on communication ability, sense of responsibility, logical thinking, teamwork spirit, responsibility and other soft skills [ 35 ]. Fig 6 shows the top professional skills required by the occupation, including data analysis ability, data sensitivity and data analysis tools such as Excel, SQL, Python and SPSS.…”
Section: Results Analysismentioning
confidence: 99%
“…Fig 5 shows the top words of core skills (general skills) required by DAPET. The abilities mentioned focused on communication ability, sense of responsibility, logical thinking, teamwork spirit, responsibility and other soft skills [ 35 ]. Fig 6 shows the top professional skills required by the occupation, including data analysis ability, data sensitivity and data analysis tools such as Excel, SQL, Python and SPSS.…”
Section: Results Analysismentioning
confidence: 99%
“…There are many publications from various fields, which use this technique to better understand the overall conditions of the studied phenomenon and, on this basis, make assessments and do further in-depth research. It is worth noting that job advertisements reflect the needs of business, the labour market and education (Calanca et al , 2019; Brooks et al , 2018; Dziobczenski et al , 2018).…”
Section: Methodsmentioning
confidence: 99%
“…In [38], the authors examined soft skills required by women and men in job ads and found that soft skills are associated with gender segregation across occupations and reinforce wage inequalities between men and women by rewarding typically "male" characteristics and penalizing "female" traits. In [139], the authors examined how job seekers react to requirements in job ads.…”
Section: ) Gender Biasmentioning
confidence: 99%